Interaction effects of high temperature and ozone on cardiovascular disease mortality in Chengdu, 2014–2023 - Yao, Jinqiu; Sun, Jingwen; Kuang, Dan; Qian, Wen; Luo, Li; Qin, Fangkui; Zhai, Yifan; Li, Yueling; Huang, Jiaqi; Wang, Cheng; Lu, Rong; Gao, XuFang (Frontiers in Public Health, 2025)
BackgroundOzone pollution has significantly worsened in recent years. In the context of global warming, the frequency and intensity of heat waves have significantly increased. Ozone levels exhibit a significant dose–response relationship with cardiovascular disease risk, and high temperatures have been demonstrated to be one of the critical risk factors for cardiovascular disease. Notably, these two hazards potentially create synergistic health impacts through combined exposure effects.ObjectivesWe aimed to estimate the interaction effects between high temperature, ozone and the death of multiple cardiovascular diseases.MethodsWe analyzed daily mortality records for cardiovascular disease types alongside meteorological and environmental parameters in Chengdu (2014–2023) through a two-stage analytical framework. In the first stage, we explored the relations between ozone exposure and multiple cardiovascular diseases, then the Distributed Lag Non-Linear Model (DLNM) was utilized to capture the lagged and cumulative effects of temperature and ozone levels on the death of different cardiovascular disease types. In the second stage, both quantitative and qualitative analyses were conducted to further explore their dose–response relationships. Additionally, stratification analyses on gender, age, education level and marital status were also performed.ResultsWe observed positive correlations between ozone levels and the death of cardiovascular disease, cerebrovascular disease, coronary heart disease, cerebral infarction, heart attack, hypertension and stroke. The highest cumulative lag effect observed was 3 days. Furthermore, the associations were stronger in women, the older adult, individuals with lower education levels, and unmarried people. High temperature and elevated ozone levels synergistically increased the mortality risk, and the relative excess risk to interaction (RERI, 95% CI) values were cardiovascular disease 0.201 (0.149–0.268), cerebrovascular disease 0.177 (0.099–0.255), coronary heart disease 0.281 (0.169–0.394), cerebral infarction 0.582 (0.369–0.794), stroke 0.287 (0.135–0.441), and 0.482 (0.269–0.694), respectively.ConclusionWe observed the synergistic interactions between ozone levels and high temperature on the death of cardiovascular disease, cerebrovascular disease, coronary heart disease, cerebral infarction, heart attack and stroke. The associations were stronger in women, the older adult, individuals with lower education levels, and unmarried people.